Objective reporting or mouthpiece for the opposition groups?: A study of malaysiakini coverage of the 2013 malaysian general election - Mohd Faizal Kasmani (Universiti Kebangsaan Malaysia Press, 2024)
Indexed by WOS/ Scopus